Zika structural genes determine the virulence of African and Asian lineages - Bruno T. D. Nunes; Camila R. Fontes-Garfias; Chao Shan; Antonio E. Muruato; Jannyce G. C. Nunes; Rommel M. R. Burbano; Pedro F. C. Vasconcelos; Pei-Yong Shi; Daniele B. A. Medeiros (Emerging Microbes and Infections)
The Asian lineage of Zika virus (ZIKV) is responsible for the recent epidemics in the Americas and severe disease, whereas the African lineage of ZIKV has not been reported to cause epidemics or severe disease. We constructed a cDNA infectious clone (IC) of an African ZIKV strain, which, together with our previously developed Asian ZIKV strain IC, allowed us to engineer chimeric viruses by swapping the structural and non-structural genes between the two lineages. Recombinant parental and chimeric viruses were analyzed in A129 and newborn CD1 mouse models. In the A129 mice, the African strain developed higher viremia, organ viral loading, and mortality rate. In CD1 mice, the African strain exhibited a higher neurovirulence than the Asian strain. A chimeric virus containing the structural genes from the African strain is more virulent than the Asian strain, whereas a chimeric virus containing the non-structural genes from the African strain exhibited a virulence comparable to the Asian strain. These results suggest that (i) African strain is more virulent than Asian strain and (ii) viral structural genes primarily determine the virulence difference between the two lineages in mouse models. Other factors may contribute to the discrepancy between the mouse and epidemic results.